Measuring Stressors Among Adolescents: Validation of the Positive and Negative Adolescent Life Experiences Scale. (December 2021) - Núñez-Regueiro, Fernando; Archambault, Isabelle; Bressoux, Pascal; Nurra, Cécile
This article develops and validates the Positive and Negative Adolescent Life Experiences (PANALE) scale, a 11-item tool that enables researchers to measure adolescent stressors in a more valid and efficient manner than existing adolescent stressors scales. The PANALE presents good psychometric qualities, in terms of construct validity (factorial structure, measurement invariance, and composite reliability) and concurrent validity with regard to eustress and distress symptoms in a French sample of high school adolescents ( N = 1513). Overall, the PANALE provides a viable alternative to existing methods for conducting quantitative research on adolescent stress processes, notably those related to school disengagement and dropout processes.